Examining the Influence of Occupational Health and Safety Practices on Work Accidents in Jordanian Industrial Companies: The Moderating Role of Work Stress - Khalaf ALQarawneh, Sulaiman Abdullah; Annan, Saher (Journal of Neonatal Surgery, 2025)
Researching occupational health and safety and the significant impact it has on the rates of work accidents and occupational injuries has become increasingly important in today's society, which has come to recognize the significance of this field. Due to the fact that it is connected to a wide variety of intricate factors, this matter is of great concern to industrial companies in Jordan and around the world. The study aimed to identify occupational health and safety and its impact on work accidents in the presence of the moderating role of work stress. A descriptive analytical research design was adopted for this study. The study used primary data sources and secondary data sources to collect data. Secondary data sources include a collection of data from books, published research, scientific journals, and university theses. Primary data sources were mainly done via a questionnaire, which was administered electronically. The researchers administered and collected the questionnaires on employees working in Jordanian industrial companies using Google Forms. Responses were collected from 300 participants. The key results of the study indicate that implementing occupational health and safety standards contributes effectively to reducing work accidents. In conclusion, studying occupational health and safety is of great scientific and practical importance, highlighting the moderating role of work stress in influencing work accidents in Jordanian industrial companies. This information is crucial for developing effective strategies to reduce occupational risks and protect worker health and safety.